Hubungan Penerapan Higiene Sanitasi Dengan Kepuasan Konsumen Pedagang Angkringan Di Kecamatan Telukjambe Timur Kabupaten Karawang - Mochammad Rifky Habib Suryanegara; Al Mukhlas Fikri (Peneliti.net, 2022)
Hygiene is a health effort by maintaining and protecting the cleanliness of the subject to protect the integrity of the food as a whole, while sanitation is a health effort by maintaining and protecting the environmental cleanliness of the subject. Angkringan is a place to sell food that is often encountered and is currently popular among the public. This study aims to determine the level of knowledge, attitudes and consumer satisfaction, the correlation of knowledge, attitude, application of hygiene and sanitation to satisfaction with consumers of angkringan traders in Kec. Telukjambe Timur Kab. Karawang. This research is quantitative using analytic observational method with cross sectional design. The number of samples is 30 angkringan using totality sampling technique and 100 consumers using accidental sampling technique. The results showed a high level of knowledge as much as 63.3%, a low level of attitude as much as 36.7%, application of poor sanitation hygiene as much as 70% and good or satisfied customer satisfaction as much as 78%. Meanwhile, there is no correlation between knowledge and the application of sanitation hygiene (p>0.05). There is a correlation between attitude and the application of sanitation hygiene (p<0.05). There is a correlation between the application of sanitation hygiene with consumer satisfaction (p <0.05). The conclusion of this study is that most of the angkringan traders have a good level of knowledge, a bad attitude level, poor sanitation practices and poor customer satisfaction. There is no correlation between knowledge and the application of sanitation hygiene. There is a correlation between attitude and the application of sanitation hygiene. There is a correlation between the application of hygiene and sanitation with consumer satisfaction.